Approccio nutrizionale all’ipofosforemia post-trapianto di rene: uno studio pilota - Alessandra Zattarin; Francesco Francini-Pesenti; Claudia Da Col; Paolo Spinella; Marianna Alessi; Lucia Federica Stefanelli; Lorenzo A. Calò (Giornale di Clinica Nefrologia e Dialisi, 2022)
Renal transplantation is the gold standard for the treatment of ESRD patients. During the early-stage post-transplantation, metabolic and electrolytic alterations may develop, including hypophosphatemia and the treatment includes a diet rich in phosphorus, sometimes with the addition of oral or intravenous phosphorus supplement. Forty-four kidney transplanted patients with hypophosphatemia were evaluated retrospectively. They were divided into two groups based on whether patients received (group A, 14 patients) or not (group B, 30 patients) dietary prescription for hypophosphatemia. Group A was further divided into two subgroups: group A1 (8 patients), with baseline phosphatemia ≥0.5 mmol/L, treated only with a diet rich in animal phosphorus, and group A2 (6 patients), with baseline phosphatemia ≤0.5 mmol/L, who received a potassium phosphate supplement in addition to the same dietary prescription. Three months after transplantation, group A had a greater increase of phosphatemia compared with group B (group A: 0.58 ± 0.12 vs 0.93 ± 0.22 mmol/L; group B: 0.59 ± 0.11 to 0.8 ± 0.13 mmol/L). Furthermore, in group A2 the increase of phosphatemia was lower than in group A1.